2019
DOI: 10.3389/fcimb.2019.00224
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Preeclampsia Is Associated With Gut Microbial Alterations in Antepartum and Postpartum Women

Abstract: Background: Imbalances in gut microbiota composition are linked to hypertension, host metabolic abnormalities, systemic inflammation, and other conditions. In the present study, we examined the changes of gut microbiota in women with early-onset preeclampsia (PE) and in normotensive, uncomplicated pregnant women during late pregnancy and at 1 and 6 weeks postpartum. Methods: Gut microbiota profiles of women with PE and healthy pregnant women in the third trimester and at 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 78 publications
6
86
1
4
Order By: Relevance
“…Two recent studies were also performed to compare GM composition and abundance between PE and HPC groups during late pregnancy [30,31]. However, our results were notably different from those obtained in these previous studies.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Two recent studies were also performed to compare GM composition and abundance between PE and HPC groups during late pregnancy [30,31]. However, our results were notably different from those obtained in these previous studies.…”
Section: Discussioncontrasting
confidence: 80%
“…Specifically, Liu et al [30] did not find significant changes in GM diversity or in the abundance of the four predominant microbes at the phylum level in patients with PE. Lv et al [31] found a different GM abundance at the genus level in patients with PE, when compared with our study. These discrepancies may reflect that following consideration: the average BP and protein urine of the PE patients in our study were notably higher than those in the previous two studies, implying that the patients in our study had more severe PE.…”
Section: Discussionsupporting
confidence: 64%
“…Another study by den Hollander et al found that Helicobacter pylori, as a cause of chronic inflammatory conditions, is associated with an increased risk of PEC (170). Further, Li Juan et al demonstrated that preeclampsia is associated with a disrupted gut microbiota composition compared with that of women who had uncomplicated pregnancies (171). In a recent review of the current knowledge about the possible association between the microbiome and the development of preeclampsia, Dunn et al did a comprehensive literature search and reported that overall, five groups of investigators studied the microbiome of PEC (172).…”
Section: Hypothesis For How Altered Microbiome Affects Pec and Iugrmentioning
confidence: 99%
“…Ruminococcus transplantation in germ-free mice enhances interferon-γ, interleukin 17, and interleukin 22 amounts [29]. Dialister was shown to be associated with antepartum preeclampsia samples [30]. Thus, the balanced steady state in the gut is likely broken in AF subjects, especially in those who suffering from recurrence.…”
Section: Resultsmentioning
confidence: 99%